Short progression‐free survival of ALK inhibitors sensitive to secondary mutations in ALK‐positive NSCLC patients. Issue 9 (23rd July 2019) - Haratake, Naoki; Seto, Takashi; Takamori, Shinkichi; Toyozawa, Ryo; Nosaki, Kaname; Miura, Naoko; Ohba, Taro; Toyokawa, Gouji; Taguchi, Kenichi; Yamaguchi, Masafumi; Shimokawa, Mototsugu; Takenoyama, Mitsuhiro
Abstract : Background: Most non‐small cell lung cancer (NSCLC) patients relapse on anaplastic lymphoma kinase‐tyrosine kinase inhibitor (ALK‐TKI) therapy because of acquired resistance. Rebiopsy is recommended to provide optimal therapy after relapse for some ALK‐TKI therapies; however, little clinical data exists on the clinical efficacy of ALK‐TKI tailored to secondary mutation. Methods: A retrospective study was conducted to analyze the patterns of ALK‐TKI treatment and clinical outcomes, including progression free survival (PFS), of ALK‐positive NSCLC patients who received rebiopsy. Based on the rebiopsy results, secondary mutations in the ALK gene that were shown to be associated with the efficacy of ALK‐TKI therapy in the preclinical or clinical setting were defined as "sensitive mutations (SM)". Results: Among 71 patients who received ALK‐TKI for NSCLC at our institution, 20 patients received rebiopsy, and secondary SM were found in eight patients. The objective response rate (ORR) of the cases with SM who received ALK‐TKI therapy was 88.9%, while the ORR of the patients without SM who received ALK TKI or chemotherapy was 20.0%; however, the PFS of the patients with SM was relatively short (with SM vs. without SM: 5.6 months vs. 5.1 months). Conclusions: The selection of ALK‐TKI based on the rebiopsy result was associated with a high ORR and relatively short PFS. The mechanism responsible for the short PFS of sensitive ALK‐TKI to secondary mutation should be clarified.